Critical Discourse Analysis on Markesot Bertutur Lagi (MBL) - Ulya Maulani Subhan; Sukarno Sukarno; Albert Tallapessy; Roni Subhan (Budapest International Research and Critics University, 2022)
Markesot Bertutur Lagi (MBL) text is a form of literary work that discusses the existence of social events in real society. The purpose of this research is to describe and analyze MBL text using critical discourse analysis on microstructure, superstructure, and macrostructure elements. The type of research used is descriptive qualitative method with the critical discourse analysis method of Teun Van Dijk. The data collection used is using the method of listening and noting. The object of this research is one of the chapters in the MBL text entitled Markesot Bertutur Hakikat Hidup. Meanwhile, the step of analyzing the data is reading and recording several sentences and words that contain elements of microstructure, superstructure, and macrostructure. Analyze and describe text into microstructure, superstructure, and macrostructure. The results of this study, firstly, in the microstructure there are syntax and semantics that have been found in several parts, including sentence form words, pronouns, coherence, and sentence meanings in some texts. Second, the plot superstructure elements that have been found are opening, conflict, solution, and closing. Third, the macro-cultural elements found in people's lives today are different from the culture in foreign countries or the author's thoughts on the text.